Laws of the Commonwealth of Pennsylvania, at 240-41, ch. 1846, § 1 (vol. 3, 1810) - (:unkn) unknown (My University, 1795)
§all gun-powder manufactured within this state, with intent to sell the same within the city or county of Philadelphia, shall be put in good and tight kegs or casks of twenty-five, fifty, or one hundred pounds neat weight , each made of well seasoned timber, bound together with at least twelve loops, and having a hole bored in each head with the diameter of one fourth part of an inch, well stopped with corks and having the tare weight (weight of the actual keg or cask) of each cask marked thereon, and that all such gun-powder, and all other gun-powder, wheresoever manufactured imported into the port of Philadelphia, or brought into the city or county of Philadelphia for sale, shall be deposited, forthwith on such importation or bringing by land or by water, in the public magazine in in the said city, and delivered to the care of the keeper the same, who shall give his receipt for the same, deliverable to the order of him or them who shall deposit the same.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER